1999
DOI: 10.1007/s100530050487
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of nanosized transition metal colloids: the influence of noble metal coating

Abstract: We present a detailed experimental study of Fe and Co colloidal particles stabilized by organic ligands. Comparison is made between the magnetic properties of pure and gold-coated particles. In all cases, evidence of superparamagnetic behaviour is found from dc susceptibility and hysteresis loops, with blocking at quite different temperatures. The magnetic anisotropy, as obtained from the blocking temperature and the coercive field, is larger for the pure particles than for the bulk material. Saturation magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 5 publications
1
22
0
4
Order By: Relevance
“…Co@Au (core@shell) NPs exhibit a reduced magnetic anisotropy compared to monometallic Co NPs [41] . However, the magnetic properties of Co@Pt NPs are similar to those for Co NPs, with a particle size similar to the size of the Co core [42] .…”
Section: Polymetallic Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co@Au (core@shell) NPs exhibit a reduced magnetic anisotropy compared to monometallic Co NPs [41] . However, the magnetic properties of Co@Pt NPs are similar to those for Co NPs, with a particle size similar to the size of the Co core [42] .…”
Section: Polymetallic Npsmentioning
confidence: 99%
“…Therefore, structural transitions in MNPs can occur as a result of changes in temperature and/or pressure ( Figure 4 ). It can be seen in Figure 4, that annealing at elevated temperatures results in the transition from Fe@Au and Co@Pt core-shell to the corresponding nanoalloy structures [41,42] . As a result of these structural changes, the annealed 6 nm CoPt NPs are FM at room temperature, while the as-synthesized Co@Pt NPs are SPM [42] .…”
Section: Polymetallic Npsmentioning
confidence: 99%
“…The obvious question is whether the nanoparticles with magnetic core and Au shell retain their magnetic properties. Paulus et al 23 have suggested that the Fe-Au nanoparticles do not retain their core-shell structure, but rather undergo mixing. On the other hand, TEM and HREM measurements of nanoparticles from a two-stage growth process using inverse micelles, by Zhou et al, 24 confirm the Fe-core/Au-shell structure but with magnetic moments similar to bulk Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Paulus et al determined a value of the anisotropy constant between 180 and 800 kJ/m 3 for Fe-Au nanoclusters of core shell structure with a diameter between 2 and 5.1 nm, respectively. 24 The value of K we estimated is of the same order of magnitude as the values determined by Paulus et al…”
Section: B Magnetic Properties Of the Nanoclustersmentioning
confidence: 91%